Differential distribution of immune checkpoints across molecular subtypes of colorectal cancer - Sofia Edin; Björn Gylling; Xingru Li; Åsa Stenberg; Anna Löfgren-Burström; Bethany van Guelpen; Agnes Ling; Ingrid Ljuslinder; Richard Palmqvist (OncoImmunology)
The recent introduction of immune checkpoint inhibitor therapy has significantly improved outcomes for patients with colorectal cancer (CRC). The most pronounced clinical benefits were observed in patients with immunogenic microsatellite instable (MSI)/deficient MMR (dMMR) tumors. However, emerging evidence indicates that a subset of patients with microsatellite stable tumors may also respond to therapy. Finding predictive markers to identify these patients is critical. In this study, we analyzed the immunohistochemical expression of immune checkpoints CTLA-4, PD-1, and PD-L1 using multispectral imaging in 151 CRC patients with defined molecular characteristics. Consistent with prior reports, MSI tumors had higher levels of all immune checkpoints analyzed than microsatellite stable tumors. Notably, distinct patterns of immune checkpoint expression were associated with KRAS and BRAF mutation status. KRAS-mutated tumors showed lower, and BRAF-mutated tumors higher, expression of immune checkpoints compared to wild-type/wild-type tumors. The strongest association with KRAS and BRAF mutations was observed for PD-L1 expression. The relationship between PD-L1 and KRAS/BRAF-mutational status was validated in a second cohort of 527 CRC patients, finding the association for PD-L1 expression in both stroma and in tumor cells. Furthermore, the role of BRAF mutation on immunity in CRC was found to be partly independent of MSI status. The strongest prognostic role was found for PD-L1 in stroma, underscoring the clinical significance of this marker. In conclusion, our findings suggest that KRAS and BRAF mutations, alongside MSI, may serve as valuable biomarkers for identifying CRC patient subgroups likely to benefit from immune checkpoint blockade in CRC.